Steel slag-bonded strand board as a carbon-negative building product. (18th July 2022) - Zod, Nada; Mucci, Alfonso; Bahn, Olivier; Provençal, Richard; Shao, Yixin
Highlights: Carbonation-activated steel slag can be used as a sole binder to produce slag-bonded strand board. Accelerated ageing tests revealed excellent performance owing to carbonate precipitation and weakly hydraulic nature of steel slag. The steel slag bonded strand boards are carbon negative, cost efficient and able to store carbon dioxide. Abstract: The feasibility of using carbonation-activated steel slag as the exclusive binder for the production of slag-bonded strand boards was studied in an attempt to replace the cement-bonded fiberboards and resin-bonded strand boards. After 12-hours of carbonation curing, the developed slag-bonded strand board displayed excellent compatibility and enhanced performance owing to the slag chemistry. Carbonated boards successfully met International Standard requirements for mechanical strength and physical performance. Durability of the composite was examined through accelerated ageing by warm water test and soak-dry cycles. Microstructure development was monitored through X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The study demonstrated that carbonation curing successfully reduced the production time, activated the dormant γ-C2 S, contributed towards superior dimensional stability, and sequestered almost 10.8 % of CO2 by dry slag mass. A further 28 days of hydration improved the mechanical characteristics of the composite and contributed towards a superior end-product. It was found that slag-bonded strand boards are resistant to ageing owing to carbonation-induced precipitation and are carbon-negative with higher carbon storage capacity and lower production cost.